2008
DOI: 10.1007/s11121-008-0105-x
|View full text |Cite
|
Sign up to set email alerts
|

Immigration Generation Status and its Association with Suicide Attempts, Substance Use, and Depressive Symptoms among Latino Adolescents in the USA

Abstract: This study investigated the relation between suicide attempts and immigrant generation status using the Latino subset of the National Longitudinal Study of Adolescent Health, a school-based, nationally representative sample. This study also examined whether generation status predicted risk factors associated with elevated suicide behaviors, namely illicit substance use, problematic alcohol use, and depressive symptoms. Finally, hypothesizing that elevated depressive symptoms and substance use mediate the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
138
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(169 citation statements)
references
References 32 publications
(39 reference statements)
20
138
6
Order By: Relevance
“…31 Specifically, it was found that both attempters and their mothers reported less mutuality and communication with each other, compared with nonattempters and their mothers. Unlike the study by Peña et al, 24 and other reports 27 indicating that US-born Latinas are more apt to attempt suicide, Zayas et al 31 did not find statistical difference between attempters and nonattempters based on birthplace.…”
contrasting
confidence: 56%
See 1 more Smart Citation
“…31 Specifically, it was found that both attempters and their mothers reported less mutuality and communication with each other, compared with nonattempters and their mothers. Unlike the study by Peña et al, 24 and other reports 27 indicating that US-born Latinas are more apt to attempt suicide, Zayas et al 31 did not find statistical difference between attempters and nonattempters based on birthplace.…”
contrasting
confidence: 56%
“…This central finding is congruent with the lower suicide rates found for first-generation Latinos across multiple national and regional cohorts of Latinos. 23,[25][26][27][28] The findings by Peña et al 24 stress the influence of generation status on suicidal behaviour. Specifically, US-born Latinos with immigrant parents (that is, second-generation youth) were more than twice as likely to attempt suicide, engage in problematic alcohol use, repeated marijuana use, and other drug use than were foreign-born youth (that is, firstgeneration youth).…”
Section: Suicidality In Latino and (Or) Hispanic Immigrant Youthmentioning
confidence: 99%
“…After adjusting for sociodemographic differences, third generation reported less lifetime alcohol use and fewer friends using alcohol, but higher intent to use alcohol and marijuana in the next 12 months, than both first and second generation. These findings are contradictory to previous reports that first generation Latina/o youth are less likely to engage in alcohol use compared with more acculturated youth [1,20,32]. Overall, healthy behaviors did not change with greater acculturation among Latinas, which also contradicts previous findings [18].…”
Section: Discussioncontrasting
confidence: 99%
“…Many of the existing studies on the correlates of suicide risk identify a variety of situational factors (Peña et al, 2008;Rew et al, 2001;Wadsworth and Kubrin, 2007). Negative life events exceptionally contribute to suicide risk (Chang et al, 2010).…”
Section: Unemployment and Suicide Behaviormentioning
confidence: 99%